A parallel algorithm for achieving the Smith Normal Form of an integer matrix - Neumann, Ingmar; Wilhelmi, Wolfgang (Parallel computing, 1996)
The Smith Normal Form of a matrix is a diagonal representation which contains the invariant factors of the matrix in its diagonal. In this paper, a new algorithm, which exploits parallelism by considering data dependencies, is proposed. In case of sparse matrices a high degree of parallelism can be reached.